Integrin and Cell Adhesion Molecules Methods and Protocols - Shimaoka, Motomu.; Shimaoka, Motomu. (Methods in Molecular Biology, 2012)
Integrins play pivotal roles not only across a wide range of physiological processes including tissue morphogenesis, immune responses, wound healing, and regulation of cell growth and differentiation, but also in numerous pathological phenomena such as autoimmunity, thrombosis, and cancer metastasis/progression. Therefore, investigations on integrins often demand multi-disciplinary approaches, making researchers long for a handy collection of comprehensive and practical protocols that detail experimental methods for studying integrin and related cell adhesion molecule functionality. Integrin and Cell Adhesion Molecules: Methods and Protocols aims to provide readers not only with basic protocols in studying integrin functions, but also with summaries on those state-of-the-art technologies that have been utilized for understanding integrin functionality at the cellular, molecular, structural, and organismal levels. Divided into six convenient sections, this detailed volume covers  basic protocols for the study of integrin and related cell adhesion molecule functionality in vitro, illustrates structural biology approaches for studying integrins and related cell adhesion molecules, focuses on emerging imaging technologies for investigating cell migration, presents strategies to elucidate signaling through cell adhesion molecules, includes experimental techniques to investigate integrin functions at organismal levels in a physiological context, and showcases the most promising methods and technologies for the development of novel therapeutics and diagnostics. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.               Both experts and non-experts in the scientific community who wish to study cell adhesion molecules and diagnostics will find Integrin and Cell Adhesion Molecules: Methods and Protocols authoritative, easily accessible, and vastly informative.